RAW MATERIAL INVENTORY PLANNING USING THE MRP (MATERIAL REQUIREMENT PLANNING) METHOD FOR POTATO CHIPS PRODUCTS (CASE STUDY OF CV. CITA MANDIRI, BATU CITY, EAST JAVA) - Nomianta, Briyan; Yoga, Tirta (Jurnal Hexagro, 2026)
The CV. Cita Mandiri is a small- and medium-sized agroindustry company that produces and markets processed snacks, including chips, sticks, opaque snacks, and fruit juice. This study aims to determine the planning of raw material inventory and forecast the company's production amount. The method of selecting respondents is purposive sampling using a key informant, such as the company's owner. Analysis using the forecasting method optimizes future raw material availability, while MRP (Material Requirement Planning) minimizes the company's pricing. The results showed that the forecasting method using moving averages was using the POM QM application for Windows version 3, MAD (Mean Absolute Deviation) 15,6, MSE (Mean Squared Error) 530,3, and MAPE (Mean Absolute Percent Error) 0,11. It is known that the results of forecasting data were obtained one year earlier, from January to December 2022, for a total production of 258.52 Kg so that the company can plan well in meeting the supply of raw materials Keywords: Forecasting, Material Requirements Planning (MRP), Inventory